(untitled) (Research, Society and Development, 2020)
Objective: to analyze in the scientific literature the managerial strategies of nurses in stimulating active fatherhood in prenatal care in primary care. Method: this is an integrative review, with a 7-year time frame, in which the descriptors were used: Primary Care, Paternity, prenatal care, health services administration, whose languages were English and Portuguese. Studies from all countries were included for a sample. The searches were carried out in the databases: Medline, Lilacs, Bdenf through the Virtual Health Library (VHL) and Cinahl. Results: 2840 articles were found, of which were selected according to criteria 48. After analyzing the studies, it was observed that the practice of using: formal and informal invitations, lectures, electronic materials, pamphlets, competitions, prizes and training to encourage active parenting in prenatal care. Conclusion: there was a lack of management strategies designed specifically by nurses to establish greater adherence to active parenting, the existence of different programs with the multiprofessional team are still insufficient for adherence to prenatal care. Being of paramount importance to encourage the development of more inclusive actions.